2022
DOI: 10.3847/psj/ac3f3d
|View full text |Cite
|
Sign up to set email alerts
|

ExoCAM: A 3D Climate Model for Exoplanet Atmospheres

Abstract: The TRAPPIST-1 Habitable Atmosphere Intercomparison (THAI) project was initiated to compare 3D climate models that are commonly used for predicting theoretical climates of habitable zone extrasolar planets. One of the core models studied as part of THAI is ExoCAM, an independently curated exoplanet branch of the National Center for Atmospheric Research Community Earth System Model (CESM), version 1.2.1. ExoCAM has been used for studying atmospheres of terrestrial extrasolar planets around a variety of stars. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 134 publications
1
37
0
Order By: Relevance
“…ExoCAM includes a two-stream correlated-k distribution RT scheme with a code lineage that traces back to Urata & Toon (2013a, 2013b and Colaprete & Toon (2003) with extensive modifications and reorganization occurring over time (Wolf & Toon 2013;Kopparapu et al 2017;Wolf et al 2022). This RT scheme, known as ExoRT, has been separated from the 3D model and is provided on GitHub 15 in order to provide an accessible 1D column model version that facilitates more rapid development and testing.…”
Section: Radiative Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…ExoCAM includes a two-stream correlated-k distribution RT scheme with a code lineage that traces back to Urata & Toon (2013a, 2013b and Colaprete & Toon (2003) with extensive modifications and reorganization occurring over time (Wolf & Toon 2013;Kopparapu et al 2017;Wolf et al 2022). This RT scheme, known as ExoRT, has been separated from the 3D model and is provided on GitHub 15 in order to provide an accessible 1D column model version that facilitates more rapid development and testing.…”
Section: Radiative Transfermentioning
confidence: 99%
“…This RT version was originally designed and tested for Archean Earthlike conditions, CO 2 amounts up to no more than 30%, Earthlike water vapor column amounts, and Sun-like stellar inputs (Wolf & Toon 2013). Later studies have found this version of the RT to overestimate the greenhouse effect from pure CO 2 atmospheres (Wolf et al 2022). Note that later iterations of ExoRT have corrected the issue with RT as is discussed in Kopparapu et al (2017) and Wolf et al (2022).…”
Section: Radiative Transfermentioning
confidence: 99%
“…CAM4 has a new deep-convection scheme relative to CAM3 (Raymond & Blyth 1986;Richter & Rasch 2008). ExoCAM is based on CAM4 but with an improved radiative transfer module modified by Dr. Eric Wolf (Wolf & Toon 2014, 2015Wolf 2017;Wolf et al 2017Wolf et al , 2022. The new radiative transfer module uses the correlated-k method (Mlawer et al 1997), and the correlated-k coefficients are calculated with access to the HITRAN 2004 spectroscopic database (Rothman et al 2005).…”
Section: Model Descriptions and Experimental Designsmentioning
confidence: 99%
“…This is because ExoCAM used in that study tends to have higher cloud decks at the terminators compared to other commonly used GCMs, while the UM tends to have lower clouds (Fauchez et al 2021b). Furthermore, ExoCAM was shown to produce consistently moister atmospheres than the UM for simulations of TRAPPIST-1e with an Earth-like atmospheric composition (Sergeev et al 2021;Wolf et al 2022), thus amplifying the potential zonal asymmetry in transmission spectra.…”
Section: East-west Terminator Differencesmentioning
confidence: 99%